Use of Curcuma longa in cosmetics: extraction of curcuminoid pigments, development of formulations, and in vitro skin permeation studies - Gisele Mara Silva Gonçalves; Gustavo Henrique da Silva; Pedro Paulo Barros; Silvana Mariana Srebernich; Cecilia Toyoko Cavalcanti Shiraishi; Victória Rodrigues de Camargos; Thais Barbiero Lasca (Universidade de São Paulo, 2014)
Curcuma longais a ginger family aromatic herb (Zingiberaceae) whose rhizomes contain curcuminoid pigments, including curcumin, a compound known for its anti-inflammatory effects. The objective of this study was to obtain curcuminoid-rich extracts, develop topical formulations thereof, and assess the stability and skin permeation of these formulations. Curcuma longa extracts were obtained and used to develop formulations. Skin permeation studies were conducted in a modified Franz diffusion cell system, and skin retention of curcuminoid pigments was quantified in pig ear membrane. Prepared urea-containing gel-cream formulations were unstable, whereas all others had satisfactory stability and pseudoplastic rheological behavior. The amount of curcuminoid pigments recovered from the receptor solution was negligible. The skin concentration of curcuminoid pigments retained was positive (>20 µg/g of skin, mostly in the stratum corneum), considering the low skin permeability of curcumin. We conclude that development of topical formulations containing curcumin or Curcuma longaextract is feasible, as long as adjuvants are added to improve preservation and durability. The formulations developed in this study enabled penetration of curcumin limited to the superficial layers of the skin and then possibly without a risk of systemic action, thus permitting local use as a topical anti-inflammatory.